2015
DOI: 10.1186/s13027-015-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic distribution of human papillomavirus (HPV) and cervical cytology findings in 5906 Thai women undergoing cervical cancer screening programs

Abstract: BackgroundCervical cancer is the major cause of morbidity and mortality in Thai women. Nevertheless, the preventive strategy such as HPV vaccination program has not been implemented at the national level. This study explored the HPV prevalence and genotypic distribution in a large cohort of Thai women.MethodsA hospital-based cervical cancer screening program at Chulabhorn Hospital, Bangkok and a population-based screening program at a rural Pathum Thani Province were conducted using liquid-based cytology and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
9
23
2
1
Order By: Relevance
“…The main finding in our study is a higher overall prevalence of HPV infection (14.4%) than previously reported from urban Nepal (8.6%) , but lower than observed in neighboring countries; a study from southeast China showed a prevalence of 23% , and in Tamil Nadu, India, a prevalence of 17% was reported . However, the overall prevalence lies within the range 7–15%, which is similar to some other Asian countries . Another major finding is a different distribution of type‐specific HPVs than reported in previous studies.…”
Section: Discussionsupporting
confidence: 51%
“…The main finding in our study is a higher overall prevalence of HPV infection (14.4%) than previously reported from urban Nepal (8.6%) , but lower than observed in neighboring countries; a study from southeast China showed a prevalence of 23% , and in Tamil Nadu, India, a prevalence of 17% was reported . However, the overall prevalence lies within the range 7–15%, which is similar to some other Asian countries . Another major finding is a different distribution of type‐specific HPVs than reported in previous studies.…”
Section: Discussionsupporting
confidence: 51%
“…In Southeast Asia, the prevalence ranged from 1.6% (Vietnam) to 13.3% (Korea). Even within a country such as Thailand, HPV prevalence can vary from 7.2% in northern region to 15.1% in central region (Kantathavorn et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In the future, the government is considering implementing the immunization of human papillomavirus (HPV) into the national immunization program [7]. Through the use of the hospital-based cervical cancer screening program at Chulabhorn Hospital, it was found that there were 4.9% abnormal Pap smear and the overall prevalence rate of HPV was 15.1% (sample size: 5,906) [8]. Thus, if this integration is successful, it could help lower the rate of cervical cancer [9].…”
Section: Gynecological Cancermentioning
confidence: 99%